Deterioration of aerodynamic performance of a train driving through noise barriers under crosswinds. Issue 231 (December 2022) - Yang, Weichao; Ouyang, Dehui; Deng, E.; Wang, Youwu; Chen, Zhengwei; He, Xuhui; Huang, Yongming
Abstract: Unilateral vertical noise barrier (UVNB), bilateral vertical noise barrier (BVNB) and fully enclosed noise barrier (FENB) are widely used along high-speed railways. The running safety of a high-speed train (HST) faces challenges when entering and exiting a noise barrier in crosswind. A series of computational fluid dynamics numerical simulations of train-noise barrier-crosswind based on the improved delayed detached eddy simulation model and 'mosaic' mesh technology are conducted. The influence of different noise barrier types on the aerodynamic load of the carriage is studied. Three buffer structures with different lengths are designed to alleviate the deterioration of aerodynamic performance of HST. Results shows that: The amplitudes of the lift force of the tail car, the lateral force and pitching moment of the head car in the BVNB are the largest, and the amplitude of the yawing moment of the head car in the FENB is the largest. Considering the engineering effects and economic benefits, a buffer structure with a length of six times head car length with a gradual ventilation rate is recommended for project, and the reduction rates of the change rates of the lift and yawing moment are 62.8% and 76.4%, respectively. Highlights: Aerodynamic characteristics of trains passing difference noise barriers are compared. The graded air permeability end structures of three types of noise barriers are designed. The buffer performance of end structures in noise barriers are analyzed.